Mechanical, morphological and thermal properties of woven polyester fibre reinforced polylactic acid (PLA) composites - M. Azlin, M. N.; Salit, Mohd Sapuan; Mohamed Yusoff, Mohd Zuhri; Zainudin, E. S. (Springer, 2022)
Polylactic acid (PLA) is derived from renewable sources and is among the most commercially available bioplastics. However, the application of PLA is limited due to its properties, such as poor thermal stability and ductility. The incorporation of woven polyester in the polymeric system has enhanced the properties of PLA. This research determines the mechanical, thermal, and morphological properties of woven polyester fiber-reinforced polylactic acid (PLA) composites. The composites were fabricated using a hot compression method with different fiber contents (%). The fiber contents used are 0 %, 20 %, 30 %, and 40 %. The WP40 composites yielded the highest tensile strength, tensile modulus, and elongation at break, which were recorded at 132.28 MPa, 976 MPa, and 17.86 MPa, respectively. The highest flexural strength for WP/PLA composites was recorded for the WP20 sample at 56 MPa. Moreover, the impact test revealed that WP30 displayed the highest strength at 61 kJ/m2. The SEM micrograph showed good adhesion between the WP-PLA composites since there was less fiber pull-out. The addition of woven polyester has improved the thermal stability and degradation behavior of the composites. All results indicate that the composites have the potential to be used in the automotive component industry. Statistical analysis has been accomplished using one-way ANOVA, displaying significant differences between the results.